Retail Mobility Environments: A methodological framework for integrating retail activity and non-motorised accessibility in Zaragoza, Spain. (January 2017) - Arranz-López, Aldo; Soria-Lara, Julio A; López-Escolano, Carlos; Pueyo Campos, Ángel
Abstract: While adequate integration of land use and transport is seen as crucial for achieving sustainable outcomes, the reciprocal interconnection between retail activity and non-motorised accessibility is yet to be adequately examined. To address this gap, this paper proposes the concept of Retail Mobility Environment (RME) and develops a methodological process for identifying and mapping RMEs, using the city of Zaragoza, Spain, as a case study. The concept of RME is developed through three methodological phases: (i) definition of non-motorised Accessibility Zones (AZs), using three indicators (walking accessibility, bicycling accessibility, betweenness); (ii) definition of Retail Zones (RZs), also using three indicators (retail density, retail diversity, retail contiguity); and (iii) definition of RMEs, where both retail activity and non-motorised indicators were weighted and combined using multi-criteria analysis. In total, four RMEs were identified and mapped: short-distance environments, motorised environments, non-motorised environments, and long-distance environments. The paper concludes with a discussion on the need to unravel the relationships between retail activity and non-motorised accessibility, in order to reach sustainable planning goals, as well as the potential usefulness of RMEs for transport policy-making.